Three-dimensional optoacoustic tomography using a conventional ultrasound linear detector array: Whole-body tomographic system for small animals - Gateau, Jerome; Caballero, Miguel Angel Araque; Dima, Alexander; Ntziachristos, Vasilis (Medical Physics, 2013)
Purpose: Optoacoustic imaging relies on the detection of ultrasonic waves induced by laser pulse excitations to map optical absorption in biological tissue. A tomographic geometry employing a conventional ultrasound linear detector array for volumetric optoacoustic imaging is reported. The geometry is based on a translate-rotate scanning motion of the detector array, and capitalizes on the geometrical characteristics of the transducer assembly to provide a large solid angular detection aperture. A system for three-dimensional whole-body optoacoustic tomography of small animals is implemented. Methods: The detection geometry was tested using a 128-element linear array (5.0/7.0 MHz, Acuson L7, Siemens), moved by steps with a rotation/translation stage assembly. Translation and rotation range of 13.5 mm and 180°, respectively, were implemented. Optoacoustic emissions were induced in tissue-mimicking phantoms and ex vivo mice using a pulsed laser operating in the near-IR spectral range at 760 nm. Volumetric images were formed using a filtered backprojection algorithm. Results: The resolution of the optoacoustic tomography system was measured to be better than 130 μm in-plane and 330 μm in elevation (full width half maximum), and to be homogenous along a 15 mm diameter cross section due to the translate-rotate scanning geometry. Whole-body volumetric optoacoustic images of mice were performed ex vivo, and imaged organs and blood vessels through the intact abdominal and head regions were correlated to the mouse anatomy. Conclusions: Overall, the feasibility of three-dimensional and high-resolution whole-body optoacoustic imaging of small animal using a conventional linear array was demonstrated. Furthermore, the scanning geometry may be used for other linear arrays and is therefore expected to be of great interest for optoacoustic tomography at macroscopic and mesoscopic scale. Specifically, conventional detector arrays with higher central frequencies may be investigated. © 2013 American Association of Physicists in Medicine.
CRIS-Team Scopus Importer:2023-03-08
Keywords: computed tomography; linear array; optoacoustic; small animal imaging; ultrasound